Calibration of Interface Induced Polarization for Full Polarimetric Ground Penetrating Radar. Issue 1 (February 2021) - Dong, Zejun; Feng, Xuan; Liu, Cai; Liang, Wenjing; Zhou, Haoqiu
Abstract: The traditional ground penetrating radar (GPR) uses only one type of antenna for data acquisition, and only obtains single polarization data of targets. It can not fully describe the various properties of the target. Full polarimetric GPR is a new technology that uses four different polarization antennas to measure the target and can receive electromagnetic waves of different polarized directions to describe the polarization effect of targets. However, when the plane electromagnetic wave propagates through the ground surface, the polarized direction will rotate, namely interface induced polarization (IIP), which results in the complex interference embedded in the full polarimetric GPR data. In this research, firstly we discuss the generation of the IIP; subsequently how the IIP affect the full polarimetric GPR data is derived; finally the calibration formula is proposed and is applied to the GPR data processing.